Protocol for a prospective mixed-methods longitudinal study to evaluate the dynamics of contraceptive use, discontinuation, and switching in Kenya - Susan Ontiri; Lilian Mutea; Maxwell Muganda; Peter Mutanda; Carolyne Ajema; Stephen Okoth; Solomon Orero; Ruth Odhiambo; Regien Biesma; Jelle Stekelenburg; Mark Kabue (BMC, 2019)
Abstract Background More women are accessing modern contraceptive use in Kenya, however, contraceptive discontinuation has stagnated over the decades. Any further increase in contraceptive use will most likely be from past users, hence understanding the dynamics of discontinuation while addressing quality of family planning services offered at health facilities and communities is critical for increasing the contraceptive prevalence rate and reducing the unmet need of family planning. The paper presents a study protocol that intends to evaluate the dynamics of contraceptive use, discontinuation, and switching among women of reproductive age initiating use of a contraceptive method. Methods This longitudinal mixed-methods study is being conducted in Migori and Kitui counties, Kenya. A formative assessment using Interviews with adolescents, older women, heterosexual couples, health care workers, and community health volunteers explored barriers to contraceptive continuation and perspectives on discontinuation utilizing a qualitative cross sectional study design. Following the formative assessment, a client-centered intervention focusing on improving quality of family planning services, including counseling, will be implemented in 10 health facilities. A 24-month prospective cohort study among women of reproductive age initiating contraception with follow-up at 3, 6, 12, and 24 months will then be undertaken to assess the discontinuation rates, examine the dynamics of contraceptive use, discontinuation and switching, and further explore barriers and enablers for contraceptive continuation and switching among the study population. Discussion In sub-Saharan Africa, contraceptive discontinuation studies have mainly been based on survey data that is collected retrospectively. By implementing a longitudinal mixed-methods study, we gain deeper insights into the contraceptive dynamics influencing the decision to continue, discontinue, and even switch following implementation of a client-centered intervention that enhances quality of care. Additionally, the study will shed more light on the profile of women discontinuing contractive use and further explore individual and couple-level dynamics influencing decision-making on continuation and discontinuation. The findings of this study will provide information that can be used to develop and implement human-centered interventions that focus on improving quality of family planning services and consequently improved continuation rates and overall satisfaction with method. Trial registration The study is registered with the Clinical Trials Registry, NCT03973593.